Oxygen isotopes of land snail shells in high latitude regions. (1st March 2022) - Nield, Catherine B.; Yanes, Yurena; Pigati, Jeffrey S.; Rech, Jason A.; von Proschwitz, Ted; Nekola, Jeffrey C.
Abstract: The present study investigates the environmental significance of the oxygen isotopic composition of several modern land snail species collected along two north-to-south transects in Alaska and Scandinavia at latitudes between 60 and 70 °N. We tested the hypothesis that land snail shell δ 18 O values primarily track precipitation δ 18 O. The results show that shell δ 18 O values from Scandinavia were ∼5.1‰ enriched in 18 O with respect to snails from Alaska, equivalent to differences in precipitation δ 18 O values between the two regions. Within the Alaskan transect, shell δ 18 O values increased with observed increasing air temperature and precipitation δ 18 O, whereas shell δ 18 O values from Scandinavia did not correlate to instrumental climate data because of a reduced climatic gradient across the locations sampled. In addition, shell δ 18 O values differed significantly among sympatric species, with larger species consistently exhibiting higher δ 18 O values, which implies that species-level isotopic variations should be considered at the local and microhabitat scale. However, when snail shell δ 18 O values from this study are combined with previously published data from North America and Europe, we see evidence that shell δ 18 O values track precipitation δ 18 O across latitudes, even when different species are combined because climate gradients are greater than variations among taxa. Highlights: This work presents the highest latitude and most negative results of modern snail shell oxygen isotopes ever reported. Oxygen isotope values of snails from polar areas track precipitation oxygen isotopes. Larger species exhibit consistently higher oxygen isotope values than smaller ones.